Biomechanics of drag and propulsion in front crawl swimming - Toussaint, H. M. (World book of swimming: From science to performance, 2012)
Swimming performance depends on the interaction of propulsive and resistive forces. A swimmer can improve by reducing resistive forces, or drag, that act on the swimming body at a given velocity or by increasing the propulsive forces. It is thus interesting to have knowledge of the backgrounds of both propulsion and drag. Especially when improvement of performance is at stake, it is interesting for the coach to know in what way it is possible to evaluate a swimmer's ability to minimize resistance and maximize propulsion. Therefore, measurement tools will be discussed that are currently used to evaluate for example the effect of suits on resistance followed by a discussion of propulsion of arms and legs in front crawl swimming.